Pulse Radiolysis Studies of Collisional Deexcitation of Ne(3P1) by H2 (Journal of Institute of Science and Technology, 2015)
The cross sections for the deexcitation of Ne(3P1) by H2 have been measured as a function of the mean collisional energy in the range of 17.3-37.9 meV or in the temperature range from 134 K to 293 K using a pulse radiolysis method as combined with time-resolved optical absorption spectroscopy. The deexcitation cross sections are in the range of 2.1- 5.6 Å2 for Ne(3P1) and nearly constant or increase slightly with increasing the collisional energy.Journal of Institute of Science and Technology, 2014, 19(1): 75-78